“Managing Risks” versus “Taking Risks”: Revisiting an Underestimated Distinction between Managers and Entrepreneurs - Cristian DÎRVĂ; Anda Simona DÎRVĂ (Eastern European Journal of Regional Studies, 2019)
The catallactic functions within a firm are the same, irrespective of production scale or organization typology. That being said, an “entrepreneurial perspective” projected on inter-/multi-/transnational corporations is just as legitimate, although usually the entrepreneurial element is associated with the “small business” managed by the owner himself. The entrepreneur, having an unmistakable role in the structure of production (still marred by ambiguities in some parts of the business literature), has the same identification data, from “self-employed” (for tax purposes) to “joint stock” companies. Every enterprise has at its core the idea of human action based on resource ownership (the property function), carried out in time (the capitalist function) and subject to uncertainty (the entrepreneurial function). These functions are related to specific business projects that are managed in a monetarily calculated manner in order to acquire profits. This article revisits the basic framework of the enterprise / corporation, placing there the entrepreneurial compound, inextricably linked to risk-taking, to which managerial activity, including risk management, is a complement, not a substitute.